Impact of Body Mass Index on Progression of IgA Nephropathy Among Japanese Patients. Issue 5 (17th August 2014) - Shimamoto, Mamiko; Ohsawa, Isao; Suzuki, Hiyori; Hisada, Atsuko; Nagamachi, Seiji; Honda, Daisuke; Inoshita, Hiroyuki; Shimizu, Yoshio; Horikoshi, Satoshi; Tomino, Yasuhiko
<x xml:space="preserve">Abstract</x> Background The impact of being overweight remains unclear in Asian populations that tend to be lean. The objective of this study is to clarify the impact of body mass index (BMI) and metabolic factors on the prognosis of Japanese patients with IgA nephropathy (IgAN). Methods A total of 193 patients with IgAN were divided into three groups equally according to BMI: Group L (lean group, BMI: 15.6–20.1 kg/m2), Group M (middle group, BMI: 20.2–23.0 kg/m2), and Group O (obesity group, BMI: 23.1–31.9 kg/m2). Clinical data at the time of renal biopsy and the progression of the patients after renal biopsy were analyzed. Results At the time of renal biopsy, hypertension, dyslipidemia, hyperuricemia, and hypercomplementemia in Group O were more significant compared with those in Group L and/or Group M. Uric acid, triglyceride, C3, C4, high‐density lipoprotein cholesterol, serum creatinine, systolic blood pressure (BP), and diastolic BP were significantly correlated with BMI. In Group O, the remission of urinary protein over 5 years was significantly delayed using a log‐rank test. At the final observation, the BMI of each group was as similar as that at renal biopsy. The patients with aggressive therapy, such as steroid therapy and/or tonsillectomy in Group O did not have major side effects, except for a slight elevation of total cholesterol and low‐density lipoprotein cholesterol. Conclusion Even slightly high BMI seems to be a risk factor for progress in Japanese patients with IgAN.